Cancer survivorship: Reproductive health outcomes should be included in standard toxicity assessments. (February 2021) - Anderson, Richard A.; Clatot, Florian; Demeestere, Isabelle; Lambertini, Matteo; Morgan, Adrienne; Nelson, Scott M.; Peccatori, Fedro; Cameron, David
Abstract: It is well established that cancer and its treatment, whether by chemotherapy, radiotherapy, hormone therapy, or surgery, can adversely impact reproductive function in both women and men. The effects of cancer treatment on reproductive function in both sexes may lead to loss of fertility, sexual desire and function, and hormone deficiency, which results in additional long-term morbidity in more than a third of patients. Given the importance of reproductive function to most people, and the often devastating effect of cancer treatment on it, we propose that proactive assessment of the functional and endocrinological impact of treatment be made a vital component of the assessment of modern cancer treatment, and should be a routine part of discussions with patients before and after treatment, both in trials and in routine care. Reproductive counselling should be proactive and encouraged, as implementation of such counselling has been shown to be beneficial to patient mental health, quality of life, and adherence to treatment. Similarly, efforts should be made to provide more adequate and accurate information to patients, as well as to offer appropriate fertility preservation approaches, which may potentially influence their treatment decisions. Highlights: Cancer therapy affects reproductive function, impacting quality of life. Potential loss of fertility is a key concern of young people with cancer. Fertility assessment should be routine in oncology clinical trials and in practice. Proper oncofertility evidence will provide insights into the risk/benefits of therapy.